Internet usage behavior among agricultural students in Haryana - MALIK, ANIL KUMAR; GODARA, A K; YADAV, KRISHAN; KUMAR, SUNIL (The Indian Journal of Agricultural Sciences, 2020)
Internet is a versatile tool used by the students for multiple purposes. A study was carried out to find the internet usage behavior among the students of CCS Haryana Agricultural University, Hisar during 2018-2019. The data were collected from 200 respondents using structured interview schedule, as personal interview schedule reduces the bias of respondents and help in collection of credible data. Findings revealed that majority of the students (71.00%) used the internet daily for more than 2 h at their hostel. Most of the students (82.50%) used internet for entertainment purpose compared to academic and professional purpose. Hence, concerted efforts like; formal education of ICT tools, easy access and usage, cost effectiveness measures, etc. have to be made by the policy makers, administrators and academicians concerned to make necessary improvements in planning and implementing ICTs strategies, so that students must be made aware of use of internet and promote interest among them for its optimum academic and professional use. Study also revealed that age, education, medium of schooling, schooling, parental income, family education, scientism, job preference, annual expenditure, mass media exposure, information seeking behavior and risk orientation with their usage behavior of internet had positive and significant correlation at 0.05 level of probability.